PARADIGMA PEMBANGUNAN EKONOMI BERKELANJUTAN BERBASIS PRINSIP HALAL DAN TAYYIB - Setiadi, Oke (Universitas Mathla’ul Anwar Banten, 2025)
This study aims to thoroughly examine the paradigm of sustainable economic development rooted in the principles of halal and tayyib. The primary focus is to analyze how the integration of Islamic values—specifically halal (permissible) and tayyib (good, pure, beneficial)—can form an economic development framework that not only fosters growth but also ensures social justice, environmental sustainability, and spiritual well-being. The specific objectives of this research include identifying the core pillars of this paradigm, understanding the challenges and opportunities in its implementation, and determining relevant measurement indicators. The research employs a qualitative method with a library research approach. Data collection involves tracing, analyzing, and synthesizing relevant scholarly literature from various sources, including accredited journals, books, proceedings, and research reports related to Islamic economics, sustainable development, and the concepts of halal and tayyib. This library research approach enables the researcher to identify existing theories, concepts, and arguments, thereby constructing a comprehensive understanding of the paradigm under investigation. The discussion results indicate that the paradigm of sustainable economic development based on halal and tayyib offers a holistic solution to the limitations of conventional development models. The discussion covers the core principles of halal and tayyib, which extend beyond mere consumption aspects to encompass the entire economic value chain. Furthermore, this research identifies significant challenges in implementation, such as global standardization and gaps in understanding, while simultaneously highlighting various opportunities, including substantial market potential and the impetus for technological innovation. This paradigm also emphasizes the need for comprehensive measurement indicators, spanning economic, social, environmental, governance, and ethical dimensions, to ensure overall sustainability and well-being.